Neuroendocrine carcinoma of the heart base in a dog: A case report - Filipejova, Zita; Agudelo, Carlos Fernando; Koskova, Benicie; Sterbova, Marie; Paninarova, Michaela; Skoric, Misa; Crha, Michal (Veterinarni medicina, 2022)
A case of a nine-year-old, intact female, American Bulldog with a heart mass is described. Echocardiography was used to identify this pathological lesion. Part of the mass and pericardial sac were surgically removed for histopathological examination. A final diagnosis of neuroendocrine carcinoma was diagnosed by necropsy and histopathology. To the author's knowledge, there is very limited information in the literature about this pathology.
Keywords: histopathology; echocardiography; cardiac tumour; heart; immunohistochemistry